The SDLC Analysis for Implementation Document Management System at IPR Center of Universitas Jenderal Soedirman - Muhammad Syaiful Aliim; Retno Supriyanti; Hari Siswantoro (Engineering, MAthematics and Computer Science (EMACS) Journal, 2023)
The Document Management System (DMS), the Center for the Development of Intellectual Property Rights, is a web-based document management information system developed by the Center for Intellectual Property Development at Universitas Jenderal Soedirman. This system is used to archive documents digitally. However, because it did not work as intended by the user, the DMS Intellectual Property Rights Center did redesign both appearance and database relations. After the redesign process is complete, the SIMD Intellectual Property Rights Centre’s development results from the redesign need to be implemented in a production environment. For the implementation process to run well, it is necessary to analyze the factors that affect the deployment process with the implementation process in the widely used System Development Life Cycle (SDLC) model. By mapping these factors with the characteristics, advantages, and disadvantages of each SDLC implementation process, the V-shaped model's deployment process is more effective and efficient in its execution in a production environment. The results show that the results of this redesign procedure can solve the problems that have occurred so far.